Nanoelectrode-mediated single neuron activation. Issue 7 (12th February 2020) - Kwon, Juyoung; Ko, Sukjin; Lee, Jaejun; Na, Jukwan; Sung, Jaesuk; Lee, Hyo-Jung; Lee, Seonghyeon; Chung, Seungsoo; Choi, Heon-Jin
Abstract : A spatially and temporally confined single neuron activation method exploiting the strong interfaces between a neuron and a nanowire electrode. Abstract : Elucidating cellular dynamics at the level of a single neuron and its associated role within neuronal circuits is essential for interpreting the complex nature of the brain. To investigate the operation of neural activity within its network, it is necessary to precisely manipulate the activation of each neuron and verify its propagation path via the synaptic connection. In this study, by exploiting the intrinsic physical and electrical advantages of a nanoelectrode, a vertical nanowire multi electrode array (VNMEA) is developed as a neuronal activation platform presenting the spatially confined effect on the intracellular space of individual cells. VNMEA makes a distinct difference between the interior and exterior cell potential and the current density, deriving the superior effects on activating Ca 2+ responses compared to extracellular methods under the same conditions, with about 2.9-fold higher amplitude of Ca 2+ elevation and a 2.6-fold faster recovery rate. Moreover, the synchronized propagation of evoked activities is shown in connected neurons implying cell-to-cell communications following the intracellular stimulation. The simulation and experimental consequences prove the outstanding property of temporal/spatial confinement of VNMEA-mediated intracellular stimulation to activate a single neuron and show its potential in localizing spiking neurons within neuronal populations, which may be utilized to reveal the connection and activation modalities of neural networks.